2015
DOI: 10.1515/intag-2015-0049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil properties on crop yield: a multivariate statistical approach

Abstract: A b s t r a c t. The aim of the study was to reveal the relationship between soil properties and grain yields in an East Hungarian region in regard to weather conditions. Soil pH, EC, carbonate content, soluble and exchangeable Na+, texture, organic carbon, and nutrient contents were analyzed. Yield data (maize, winter wheat, sunflower) from 10 years were standardized using calculated relative yield and yield variability. Weather conditions were characterized by the Pálfai Drought Index. Hydrological and topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 16 publications
(19 reference statements)
1
28
0
4
Order By: Relevance
“…In this sense, the use of machine learning tools may accelerate the identification of data for characterizing soils. Several methods of analyzing large amount of data of both continuous and categorical variables have been used in works of various natures, such as the stepwise multiple linear regression (SMLR) (Juhos;Szabó;Ladányi, 2015;Menezes et al, 2016;Rodrigues;Corá;Fernandes, 2012). This analysis adjusts regression models from easily obtained variables to estimate data more difficult to be acquired, in which the addition or removal of predictive variables to the model is performed based on statistical tests, generating a final equation.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the use of machine learning tools may accelerate the identification of data for characterizing soils. Several methods of analyzing large amount of data of both continuous and categorical variables have been used in works of various natures, such as the stepwise multiple linear regression (SMLR) (Juhos;Szabó;Ladányi, 2015;Menezes et al, 2016;Rodrigues;Corá;Fernandes, 2012). This analysis adjusts regression models from easily obtained variables to estimate data more difficult to be acquired, in which the addition or removal of predictive variables to the model is performed based on statistical tests, generating a final equation.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of intensive agrochemical application, environmental impacts on soils are increasing parallel with loss of abundance and diversity of living organisms (Johnston, 1986;Varga et al, 2007). One of the most important requirements, therefore, is the sustainable farming practices and food production with the need to reduce the use of artificial chemicals and stimulants (Juhos, 2014;Juhos et al, 2015Juhos et al, , 2016Tariq et al, 2016). With those conditions consumers' highlighted expectation for healthy and chemical-free foods are also required.…”
Section: Introductionmentioning
confidence: 99%
“…understanding the variability of landscape and soil characteristics and their influences on crop productivity is a vital and critical component of the site-specific and sustainable management system and land use planning, (Juhos et al, 2015). The expectable yield or productivity capacity is useful in assessing the soil suitability for agricultural use.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, (Mbodj et al, 2004), in Oud Rmel Catchment of Tunisia, found that the most influential limiting factors were alkaline pH and the excessive amount of the soil calcium carbonate. Multiple statistical procedures have been developed to presage the crop yield, the fitness of these procedures relies on the framework and size of the database, but each method has its own limitations, (Juhos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%